CORELATION BETWEEN DURATION OF CATHETERIZATION AND PAIN INTENSITY IN PATIENTS WITH URETHRA CATHETERIZATION - Komang Agus Jerry Widyanata; Catur Budi Susilo; Cristin Wiyani (Bali Health Published Journal, 2019)
Background: Urinary catheterization is a medical action that is often carried out for diagnostic and therapeutic purposes. One side effect of catheter placement is pain. Pain felt during catheter placement due to urethral trauma. Pain can be affected by the length of time the catheter is attached. The results of a preliminary study of 5 different patients who were attached to a catheter at different times had different pain intensities. Objective: To find out the relationship between the length of time the catheter is attached to the pain intensity of a patient with a urethral catheter. Method: This study is a non-experimental study with a cross sectional approach. The sampling technique used was Purposive Sampling and the sample size was 38 people. Data collection tools use observation sheets and numeric rating scale (NRS) to assess pain intensity. Bivariate analysis using Pearson Product Moment correlation analysis. Results: The length of time the catheter is installed is at most two days and one day which are 21.1% and 18.4%, respectively. The pain intensity of patients with urethral catheters in the lightest category is 42.1% while the moderate and heavy categories are the same in the amount of 26.3%. The results of bivariate analysis obtained the value of the correlation coefficient (r) of -0.914 with p value 0,000 (p <0.05). Conclusion: There is a significant negative relationship between the difference in catheter-attached time and the pain intensity of a patient with a urethral catheter where the longer the catheter is attached, the less pain is felt.